STRATEGI DIGITAL MARKETING MELALUI KEY OPINION LEADER PADA BRAND GETAL ORIGINAL - Khoirunisa, Fathiya; Supama Wijaya, Abung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the application of digital marketing strategies through collaboration with Key Opinion Leaders (KOLs) for the Getal Original brand. KOLs play an important role in strengthening communication between brands and consumers through creative content that can increase brand awareness, trust, and customer loyalty. This study uses a descriptive approach with observation, interviews, active participation, and literature study methods conducted during an internship at Sinergi Mumtaz Group. The analysis was carried out using the SOSTAC (Situation, Objective, Strategy, Tactic, Action, Controlling) theoretical framework to assess the planning, implementation, and evaluation of the collaboration strategy with KOLs. The results of the study show that KOL collaboration significantly helps Getal Original expand its audience reach, increase sales, and maintain brand image consistency in digital media. In addition, maintaining long-term relationships with KOLs through intensive communication and incentives plays an important role in maintaining the sustainability of the collaboration.